Agricultural diversification and smallholders in South Asia - Joshi, Pramod Kumar; Gulati, Ashok; Cummings, Jr. , Ralph (Academic Foundation, 2007)
Pro-poor opportunities are rapidly unfolding in South Asia, spurred by new lifestyles and tastes, stimulated by increasing incomes, spreading urbanisation, and expanding globalisation. Dietary patterns are changing of both the poor and the rich, as well as rural and urban consumers, from staple foodgrains to high-value-commodities such as fruits, vegetables, milk, meat, eggs, and fish. The real challenge is how to grab these opportunities to alleviate poverty and improve quality of life, particularly for smallholders. This book, Comprising contributions by experts from various countries, the book provides a range of information, analysis, and the beginnings of pathways to accelerate agricultural diversification and facilitate inclusiveness of small holders through correcting incentives, evolving institutions, and developing infrastructure.